2017
DOI: 10.1016/j.poly.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Dioxidomolybdenum(VI) and –tungsten(VI) complexes with tetradentate amino bisphenolates as catalysts for epoxidation

Abstract: Sixteen molybdenum and tungsten complexes with tripodal or linear tetradentate amino bisphenol ligands were studied as catalysts for the epoxidation of cis-cyclooctene, 1-octene, styrene, limonene and α-terpineol. These complexes can be divided into different categories upon key features, i.e. central metal (Mo vs. W), side-arm donor (O vs. N), hybridization of the N-donor (pyridine vs. amine), ligand geometry (tripodal vs. linear diamine) and sterical hindrance (Me vs. tert-Bu substituents in the phenol part)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…Comparative studies for the isostructural W and Mo analogues 1 and 4, respectively, indicated superior performances for the molybdenum catalyst using H 2 O 2 or tbhp. Several literature studies reported higher catalytic activity of molybdenum compounds than the tungsten analogues using tbhp [18,22,[28][29][30][31][32][33][34][35] or H 2 O 2 , [22,28,35,36] as verified in the present work. Mo versus W analogues may possess different M = O bond strengths (which may be weaker for molybdenum counterparts) [37] On the other hand, the influence of the type of oxidant on the types of active species formed in situ for olefin epoxidation in the presence of molybdenum catalysts was demonstrated in theoretical studies [31,38].…”
Section: Catalytic Epoxidationsupporting
confidence: 85%
“…Comparative studies for the isostructural W and Mo analogues 1 and 4, respectively, indicated superior performances for the molybdenum catalyst using H 2 O 2 or tbhp. Several literature studies reported higher catalytic activity of molybdenum compounds than the tungsten analogues using tbhp [18,22,[28][29][30][31][32][33][34][35] or H 2 O 2 , [22,28,35,36] as verified in the present work. Mo versus W analogues may possess different M = O bond strengths (which may be weaker for molybdenum counterparts) [37] On the other hand, the influence of the type of oxidant on the types of active species formed in situ for olefin epoxidation in the presence of molybdenum catalysts was demonstrated in theoretical studies [31,38].…”
Section: Catalytic Epoxidationsupporting
confidence: 85%
“…The mass and IR spectra (see below) show that the addition of either H 2 [ 16 O] or H 2 [ 18 O] in the reaction mixture leads to the clean formation of the respective isotopologue which demonstrates that the formation of dioxidotungsten centre is caused by the hydrolysis reaction wherein the included water acts as the oxide source. The molybdenum complex Mo 16 O 2 (L) was prepared by the reaction of sodium molybdate with the ligand precursor H 2 L in an acidic methanol solution . The 18 O enriched complex Mo 18 O 2 (L) was obtained straightforwardly by heating Mo 16 O 2 (L) with an excess of H 2 [ 18 O] in methanol solution and allowing the complex to crystallize upon cooling (Scheme b).…”
Section: Resultsmentioning
confidence: 99%
“…The molybdenum complex Mo 16 O 2 (L) was prepared by the reaction of sodium molybdate with the ligand precursor H 2 L in an acidic methanol solution. [26] 13 C NMR spectroscopy, which show expected chemical shifts for the octahedral complexes with C 2 rotation axis. [13,25] The isotopic purity of the compounds was unequivocally confirmed by mass spectrometry.…”
Section: Syntheses and Reactivitymentioning
confidence: 99%
See 2 more Smart Citations